Electrolysis Process of Acid Acetic and Sugar Water Solution as an Alternative Fuel - Gatot Soebiyakto; Sutrisno Sutrisno; Dadang Hermawan; Muhammad Ghazali Arrahim (Widyagama University of Malang, 2023)
One alternative energy that can be developed is hydrogen. To obtain hydrogen gas by decomposing water compounds (H2O) into hydrogen hydrogen oxygen gas (HHO) through electrolysis. The solution used in this electrolysis process uses sodium chloride (NaCl) with electric current energy. In this research, a dry cell type HHO generator was used, the electrode used was a type 304 stainless steel plate with a catalyst percentage (NaCl) of 8%, 10%, 12%, 14% and 16%. The aim of this research is to determine the hydrogen content in a solution of vinegar and sugar water which can be used as an alternative fuel. This research produced the highest hydrogen volume at a percentage of 16% of 367 mL at the highest temperature of 547 C, the lowest 317 C and the lowest hydrogen volume of 198 mL. The highest flame height is 5.72 cm and flame width is 2.98 cm and the highest flame brightness level (Red Green Blue) is 16 RGB and the lowest brightness level is 2 RGB.